PERAN DAN TANTANGAN PEREMPUAN DALAM MEWUJUDKAN MODERASI BERAGAMA DI INDONESIA - Wahid, Annisa; Rosyad, Rifki (ILJ: Islamic Learning Journal, 2023)
Since the enactment of Regional Autonomy in Indonesia, intolerance has continued to increase in various regions. This can be seen from the rampant cases of terrorism and radicalism that have penetrated Indonesian society. Indonesia is ranked 37th with the highest cases of terrorism and radicalism globally. This of course raises a lotiloss, not onlyimaterial but also the psychological and mental health of people who are worried about the safety of their lives. The government has made various efforts to reduce cases of intolerance (such as radicalism and terrorism) and maintain inter-religious harmony. One way is by echoing the concept of religious moderation. Realizing religious moderation requires the active role of all parties, including women. Women have great potential in realizing and maintaining the tolerance that is needed in this diverse Indonesia. This study aims to highlight the role of women and the challenges faced by women in realizing religious moderation in Indonesia. This study uses a literary method in the form of a qualitative descriptive method using gender theory. The results of this study indicate that the role of women will be the basic capital in realizing moderation in themselves, their families and society. In realizing religious moderation, women face challenges such as the occurrence of gender gaps, subordination, multiple roles and gender stereotypes.